Growth Inhibition of Streptomyces Species by l-Serine and Its Effect on Tetracycline Biosynthesis - Parada, Jose L. (1981)
The addition of serine to minimal medium inhibited the growth of Streptomyces aureofaciens and Streptomyces rimosus. Both the outgrowth of spores and the growth of vegetative cells were inhibited by l-serine. This effect was independent of the carbon source used. In rich nutrient medium, however, the serine effect was not observed. The presence of glycine and methionine in minimal medium reversed the growth inhibition imposed by serine, suggesting that a metabolic block related to the synthesis of these two amino acids was involved. A serine-tolerant mutant of S. aureofaciens isolated after ultraviolet irradiation showed a level of serine deaminase comparable to that of the wild-type strain, which indicated that tolerance to serine was not due to the presence of a more active deaminating enzyme in the mutant. Serine markedly reduced tetracycline and oxytetracycline biosynthesis with the parental strains of Streptomyces spp. The serine-tolerant mutant, however, produced almost the same amount of tetracycline in the presence or absence of serine. The final cell population in fermentation broth was not significantly reduced by l-serine, and the addition of glycine and methionine did not increase the tetracycline yields, which suggested that l-serine inhibition of antibiotic biosynthesis was by a mechanism different from that related to growth inhibition.